Clinicopathological evaluation of crescentic glomerulonephritis: a retrospective single-center study - Ahmet Dogukan Kansu; Murvet Yilmaz (The Egyptian Journal of Internal Medicine, 2026)
Abstract Aim Crescentic glomerulonephritis (GN) represents a group of diseases characterized by rapid and severe kidney damage within weeks or months. This study aimed to evaluate the demographic, laboratory, histopathological features, treatment approaches, and renal survival of patients with crescentic GN followed in a nephrology clinic. Materials and methods Eighty patients with crescentic glomeruli identified on kidney biopsy were retrospectively analyzed. Five patients were excluded due to transplantation biopsies, insufficient data, or follow-up shorter than 6 months. Demographic, laboratory, histopathological, and treatment data were obtained from hospital records. Patients were grouped by immunohistological subtype: group IAb (anti-glomerular basement membrane disease), group IIAb (immune complex-mediated crescentic GN), and group IIIAb (pauci-immune crescentic GN). They were also divided based on the proportion of crescents: group I% (< 50%) and group II% (> 50%). Results Among the patients, 28 (37.3%) were female and 47 (62.7%) were male, with a mean age of 52.36 ± 16.70 years. Group IIIAb was the most common (53.3%), and group IAb was rare (1.3%). Group IIIAb patients had higher serum urea and creatinine and lower eGFR than group IIAb. Mean follow-up was 24.24 ± 17.49 months. Renal replacement therapy (RRT) was initiated in 14.7% of group IIAb and 15% of group IIIAb patients ( p = 0.972). RRT was more frequent in patients with > 50% crescents (41.2%) than those with < 50% (6.9%) ( p = 0.004). A crescent rate > 50% was associated with a significantly higher need for renal replacement therapy. Conclusion Pauci-immune GN is the most frequent subtype and is associated with poorer baseline renal function; a crescent burden > 50% was associated with a significantly higher need for renal replacement therapy.